Analysis of a Family with Brugada Syndrome and Sudden Cardiac Death Caused by a Novel Mutation of SCN5A - Yao-Bin Zhu; Jian-Hui Zhang; Yuan-Yuan Ji; Ya-Nan Hu; Han-Lu Wang; Dan-Dan Ruan; Xiao-Rong Meng; Xin-Fu Lin; Jie-Wei Luo; Wei Chen (Cardiology Research and Practice)
Background. Brugada syndrome is a hereditary cardiac disease associated with mutations in ion channel genes. The clinical features include ventricular fibrillation, syncope, and sudden cardiac death. A family with Brugada syndrome with sudden cardiac death was analyzed to locate the associated mutation in the SCN5A gene. Methods and Results. Three generations of a Han Chinese family with Brugada syndrome were recruited in the study; their clinical phenotype data were collected and DNA samples extracted from the peripheral blood. Next-generation sequencing was carried out in the proband, and candidate genes and mutations were screened using the full exon capture technique. The family members who participated in the survey were tested for possible mutations using Sanger sequencing. Six family members were diagnosed with Brugada syndrome, including four asymptomatic patients. A newly discovered heterozygous mutation in the proband was located in exon 25 of SCN5A (NM_000335.5) at c.4313dup(p.Trp1439ValfsTer32). Among the surviving family members, only those with a Brugada wave on their electrocardiogram carried the c.4313dup(p.Trp1439ValfsTer32) variant. Bioinformatics prediction revealed that the frameshift of the c.4313dup (p.Trp1439ValfsTer32) mutant led to a coding change of 32 amino acids, followed by a stop codon, resulting in a truncated protein product. Conclusion. The newly discovered mutation site c.4313dup(p.Trp1439ValfsTer32) in exon 25 of SCN5A may be the molecular genetic basis of the family with Brugada syndrome.